Un modelo de dirección democrático y participativo = A democratic and participative model of principalship - Sala, Juan Salame (Educação)
This text presents the idea that the educational systems reflects the history and culture of their own countries. Relate the democratic selection of principal in Spain to its recent history. Enfatize the limitationes of the system and the difficulties to change and evaluate it in a systematic way. Idenfify the contradictions of the Spanish system of selection of principals and the need of better preparations for the principals